2022
DOI: 10.1128/spectrum.02004-21
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the Structure and Function of the Pig Manure Bacterial Community after Enrofloxacin Exposure

Abstract: A stable intestinal bacterial community balance is beneficial for animal health. Enrofloxacin is widely used in animal husbandry as a therapeutic drug, but it can cause intestinal environmental imbalance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The species Terrisporobacter petrolearius JCM 19845 T , isolated in 2015 from a petroleum reservoir sample from an oilfield in Shengli (China) ( Deng et al, 2015 ), and Terrisporobacter hibernicus NCTC 14625 T , isolated in 2023 from bovine feces, were both described as non-acetogenic species ( Mitchell et al, 2023 ). The genus Terrisporobacter has been found strongly associated with manure ( Chen et al, 2022 ) and was shown to represent a key player in the degradation of manure by fermenting carbohydrates to H 2 + CO 2 and acetate ( Budianto and Yasin, 2024 ). Correspondingly, biotechnological applications of bacteria from the genus Terrisporobacter have focused on their H 2 -producing capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The species Terrisporobacter petrolearius JCM 19845 T , isolated in 2015 from a petroleum reservoir sample from an oilfield in Shengli (China) ( Deng et al, 2015 ), and Terrisporobacter hibernicus NCTC 14625 T , isolated in 2023 from bovine feces, were both described as non-acetogenic species ( Mitchell et al, 2023 ). The genus Terrisporobacter has been found strongly associated with manure ( Chen et al, 2022 ) and was shown to represent a key player in the degradation of manure by fermenting carbohydrates to H 2 + CO 2 and acetate ( Budianto and Yasin, 2024 ). Correspondingly, biotechnological applications of bacteria from the genus Terrisporobacter have focused on their H 2 -producing capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of bacteria to enrofloxacin is important at both the public health and pig health levels, as it is still commonly used in most countries, despite its public health importance being as high as that of colistin [ 14 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under enrofloxacin stress, the structure of the fecal bacterial community in pigs changes, with a significant increase in the abundance of Firmicutes . Furthermore, enrofloxacin-induced differences in the intestinal flora were found to be fully recovered 10 days after the discontinuation of the drug ( 21 ). Moreover, corticosterone can affect carbohydrate metabolism and amino acid metabolism in chicks by altering gut microbes ( 22 ).…”
Section: Introductionmentioning
confidence: 99%